PAW patrol. Aqua pups [videorecording (DVD)] - Chapman, Keith, 1958- (Paramount, 2023)
The PAW Patrol returns to the magical, underwater city of Puplantis! When an unhappy Mer-pup named Moby tries to float Puplantis to the surface, it's up to the PAW Patrol and Skye's cousin Coral to stop him and save the city. Next, the pups participate in a big Mer-race and must come to the rescue when Moby's cheating threatens Puplantis. Then Moby swipes the Whale Patroller, and with the help of sea creatures, the pups chase it down, plus so much more underwater adventure!